Anticholinergics for asthma: a long history. Issue 1 (February 2018) - Rodrigo, Gustavo J.
Abstract : Purpose of review: To provide a fast overview about the introduction and development of anticholinergic drugs in Western medicine to their current indications particularly in asthma. Recent findings: Although short-acting muscarinic antagonists have been positioned in the last 15 years for the treatment of adults and children with moderate-to-severe acute asthma in the emergency setting (reducing the risk of hospital admissions and improving lung function), a growing body of evidence has recently emerged that positions the long-acting muscarinic anticholinergic tiotropium bromide as add-on therapy to at least inhaled corticosteroids (ICS) maintenance therapy in adults, adolescents, and children with symptomatic asthma. Thus, the addition of tiotropium bromide to ICS alone or ICS and another controller was associated with significant improvements in spirometric measures and asthma control, and a significantly decrease in the rate of asthma exacerbations. Summary: Short-acting muscarinic antagonists and tiotropium bromide have a well established role in the treatment of different phases of asthma. Further data are needed to provide more evidence on other selective long-acting muscarinic antagonists in addition to tiotropium as potential treatment options.